Petunidin-Based Anthocyanin Relieves Oxygen Stress in Lactobacillus plantarum ST-III - Yan, Minghui; Wang, Bing-hua; Fu, Xiaofei; Gui, Min; Wang, Guojiao; Zhao, Lei; Li, Ruiying; You, Chunping; Liu, Zhenmin (Frontiers in Microbiology, 2020)
Application of probiotics in the food industry has been hampered by their sensitivity to challenging conditions that reduce their vitality in food matrices. A lot of attempts have been made to promote the growth of these probiotics in the aspect of nutrition demands. Among the other adverse conditions, oxygen stress can restrict the growth of probiotics and has not yet been paid enough attention to. In this study, the effect of a petunidin-based anthocyanin (ACN) on the growth of probiotic Lactobacillus plantarum ST-III was investigated under oxygen stress. The growth of ST-III was analyzed through spot assay on agar plates as well as plating-based enumeration of the viable cells in the liquid culture. Results indicated that ACN could efficiently improve the growth of ST-III under oxygen stress, whereas no effect was observed in the absence of oxygen stress. Further investigations indicated that ACN reduced the oxido-reduction potential of the culture, meanwhile, it exerted a positive transcriptional regulation on the thioredoxin system of ST-III, leading to a decrease in reactive oxygen species accumulation within the cells. Moreover, ACN enabled the growth of ST-III in reconstituted skim milk and promoted the formation of milk clots. These results revealed the role of a petunidin-based anthocyanin in oxygen stress relief and highlighted its potential in manufacture and preservation of L. plantarum-based dairy products.